Algebraic detection and identification of parameter faults for robots - Lomakin, Alexander; Deutscher, Joachim (At-Automatisierungstechnik, 2021)
In this paper, a new algebraic method for the detection and identification of parameter faults for robots is presented. The proposed approach is independent of occurring disturbances and additionally allows to determine the detectable faults. The method is based on the reconstruction of the residual as a nonlinear differential algebraic expression using polynomial approximation. This results in an approach for fault detection, identification and analysis, which can be efficiently realized with FIR filters using solely measurable signals. The presented method is applied to a SCARA robot and validated by simulation.
CRIS-Team WoS Importer:2021-08-27